Improved Specimen-Referral System and Increased Access to Quality Laboratory Services in Ethiopia: The Role of the Public-Private Partnership - Kebede, Yenew (J Infect Dis, 2016)
Background. Nonstandardized specimen-transport logistics, lack of laboratory personnel to transport specimens, lack of standard specimen containers, and long turnaround time (TAT) hindered access to quality laboratory services. The objective of the Becton, Dickinson, and Company (BD)–US President's Emergency Plan for AIDS Relief (PEPFAR) Public-Private Partnership (PPP) was to support country-specific programs to develop integrated laboratory systems, services, and quality improvement strategies, with an emphasis on strengthening the specimen-referral system (SRS). Methods. In 2007, through the Centers for Disease Control and Prevention (CDC), the Ethiopian Public Health Institute (EPHI) joined with the BD-PEPFAR PPP to strengthen laboratory systems. A joint planning and assessment committee identified gaps in the SRS for prioritization and intervention and piloted the system in Addis Ababa and Amhara Region. Results. The PPP established standardized, streamlined specimen logistics, using the Ethiopian Postal Service Enterprise to support a laboratory network in which 554 facilities referred specimens to 160 laboratories. The PPP supported procuring 400 standard specimen containers and the training of 586 laboratory personnel and 81 postal workers. The average TAT was reduced from 7 days (range, 2–14 days) to 2 days (range, 1–3 days) in Addis Ababa and from 10 days (range, 6–21 days) to 5 days (range, 2–6 days) in Amhara Region. Conclusions. This study highlights the feasibility and untapped potential of PPPs to strengthen laboratory systems. This planned and structured approach to improving specimen referral enhanced access to quality laboratory services.